3(X+2)+7=2(X+3)+6

Simple and best practice solution for 3(X+2)+7=2(X+3)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(X+2)+7=2(X+3)+6 equation:


Simplifying
3(X + 2) + 7 = 2(X + 3) + 6

Reorder the terms:
3(2 + X) + 7 = 2(X + 3) + 6
(2 * 3 + X * 3) + 7 = 2(X + 3) + 6
(6 + 3X) + 7 = 2(X + 3) + 6

Reorder the terms:
6 + 7 + 3X = 2(X + 3) + 6

Combine like terms: 6 + 7 = 13
13 + 3X = 2(X + 3) + 6

Reorder the terms:
13 + 3X = 2(3 + X) + 6
13 + 3X = (3 * 2 + X * 2) + 6
13 + 3X = (6 + 2X) + 6

Reorder the terms:
13 + 3X = 6 + 6 + 2X

Combine like terms: 6 + 6 = 12
13 + 3X = 12 + 2X

Solving
13 + 3X = 12 + 2X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-2X' to each side of the equation.
13 + 3X + -2X = 12 + 2X + -2X

Combine like terms: 3X + -2X = 1X
13 + 1X = 12 + 2X + -2X

Combine like terms: 2X + -2X = 0
13 + 1X = 12 + 0
13 + 1X = 12

Add '-13' to each side of the equation.
13 + -13 + 1X = 12 + -13

Combine like terms: 13 + -13 = 0
0 + 1X = 12 + -13
1X = 12 + -13

Combine like terms: 12 + -13 = -1
1X = -1

Divide each side by '1'.
X = -1

Simplifying
X = -1

See similar equations:

| 6k-2k+6m= | | 8x^4-16x^3+40x^2= | | 17x-y=90 | | 6-2-7+3l= | | 180-x=18+3(90-x) | | (2x+3)(x^2-8x+15)=0 | | 25-0.02w=12.08 | | 0=3x^2+24x-27 | | 40=-.005x^2+1.2x-72.7 | | (4x+8)-(7x-8)= | | 25-0.02=12.08 | | 30-12+45+-10-7= | | -33x(8y)/66x | | 5(x-3)+66=5x-10 | | 8n^2+6n+2=0 | | 4x+106+142+175+98+105+100=900 | | D^3-9=503 | | 40=x^2-240x+14540 | | 3n+3=-255 | | d=16(5) | | 7y+20=2y | | -7x+2y=-10 | | -46/40-6/5-1.65 | | 24-(36-15)-12-12= | | 115+x+75+130+x+90+130+x+65+x+80=900 | | 8+2t=12 | | 5(6-8h)= | | -2+r=r-2+2r | | y=-1x+45 | | 2m+4m=24m | | 4w/3=36 | | 3h+4=4h-(h-3) |

Equations solver categories